Formation of High School Students' Civic Competence in the Context of Ethno-Cultural Traditions - Gayane Poghosyan; Anahit Gasparyan; Nurdiana Nurdiana; Muhammad Ridwan; Bakhrul Khair Amal (BIRCU, 2020)
The goal of the research is to increase the civic competence of students in educational institutions by involving ethno-cultural traditions. All over the world, national problems have aggravated, conflicts have arisen, for the solution of which new forms of intercultural and interethnic interactions are needed. Within the framework of the study, the situation was analyzed, the cultural traditions and values of the Armenian, as well as of peoples’ living in Armenia were studied, a two-stage sociological study was carried out, its results were analyzed and relevant recommendations were made. From the analysis of the results it became clear that the study of the traditions and habits leads to the development of the culture of one's own people և other nations and love, responsibility and an attitude towards the Motherland and the Country is formed. Society has an objective need to form a competent citizen, who will be able to implement civil rights and obligationsin the best way, who will have civil position and participation in the processes taking place in the country. The ethnocultural habits directly contribute to the formation of students' civic competence, and the incusion of them into educational institutions will create potential opportunities for that. In order to build civic competence, first it is need to deveop skills among learners and educators who, in different life conditions (including crisis and risk), in various educational situations (as well as self-educational), will be able to make decisions, identify problems and propose solutions, as well as take targeted and responsible actions, developing creative and critical thinking.